La educación inclusiva en el desarrollo integral de los estudiantes con capacidades diferentes del tercer y cuarto año de educación básica de la Escuela Fiscal Mixta "Sofía Alarcón De Espín", recinto Nueva Fortuna, parroquia Caracol, cantón Babahoyo, provincia de Los Ríos en el periodo 2011 - 2012 - Guerra Villegas, Tanya Karina (2012)
This paper is entitled "Inclusive Education in the overall development of students with disabilities in the third and fourth years of basic education of Fiscal Primary School" Sofia Alarcon Spin "new fortune enclosure, parish snail, Canton Babahoyo Los Rios province, members of the research team are Ms. Tanya KarinaWard Villegas and Ms.Zoila Patricia Salvatierra Acosta, who wish to include students with special educational needs in regular education. Through research students of the 3rd and 4th year of basic education, teachers and parents, we could detect that there were children with disabilities who were excluded for various situations thus preventing the full development and break paradigms that exist in school and in society. For a better understanding of the problems in research have translated into the different Scientific Theoretical Framework theoretical underpinning inclusive education in the appearance Physiological, Psychological, Psychosocial, Sociocultural, and Sociological Ontogenesis, we also focus on the overall development and for this we draw on theories of constructivism Psychogenetic as Jean Piaget and Cognitive Approach in Psychology Cognitivist. With respect to the methodological strategies we used, for the purpose it was applied, the level of knowledge is descriptive, the place is bibliographical and field and the technique used for the collection of information is the surveys that perform a universe of 41 students, 6 teachers and 40 parents of families for a total of 87 people. With the results of the research tabulated by statistical graphics as bar charts and performed the analysis and interpretation of information individually, it was so allowed us to conclude that most teachers want to be trained in dynamic methods to include students with special educational needs, students and parents believe that the game in the process of school will be an innovative way to interact because it helps to strengthen and consolidate the knowledge of an active and dynamic. For this reason we believe in the importance of inclusive education in the overall development it can be done using games as a human activity that helps the relationship of children with or without special educational needs, thus forming a humanistic society without paradigms.